College life is stressful today – Emerging stressors and depressive symptoms in college students. Issue 7 (3rd October 2018) - Acharya, Lala; Jin, Lan; Collins, William
ABSTRACT: Objective: The study identified important stressors associated with depressive symptoms in college students across the subgroups of gender and domestic/international status, and compared between-group differences across stress levels. Participants: Data were collected from 631 undergraduate students from October 2014 to March 2015. Methods: Participants completed an online survey containing measures of stressors (Student-Stress-Survey), depressive symptoms (CES-D scale), and demographics. Results: The mean CES-D score (16.24) of sample indicated high depressive symptoms. International students reported higher depressive symptoms than domestic students and students identifying as female showed higher depression symptoms than male. Eight most frequently occurring stressors experienced by over 50% of the sample were identified as important; differences in stress levels across gender and domestic/international status were discussed. Conclusions: This renewed look reinforced that tailored and sustained efforts are needed to address the continued prevalence of different stressors and associated depressive symptoms faced by college students on US campuses.